Taxonomy and morphologies of Undaria pinnatifida (Phaeophyceae, Laminariales) in Golfo Nuevo, Argentina - Casas, Graciela Noemi (2020)
Since 1992, after the accidental introduction of Undaria pinnatifida (Phaeophyceae, Laminariales) and its subsequent dispersion along the coasts of Argentina, the species has become part of the local benthic marine flora. In this note, after reviewing the background of Undaria, the taxonomic position of the forms found in Golfo Nuevo (Argentina) can be confirmed and the observed morphotypes discussed.